Pengekalan dan peralihan bahasa dalam kalangan Orang Batak Toba di Pontianak, Indonesia / Hotma Simanjuntak - Hotma , Simanjuntak (2017)
The use of Batak Toba language in Pontianak, now is more and more decrease. The Batak people cannot maintain the presence of their language against the local people that is classified majority. The Batak Toba people choose Indonesian when they speak with local community, and also Indonesian too when they speak among family and relative members in family environment. The above fact was found out based on the study on the language maintenance and shift among the Batak Toba people in Pontianak, Indonesia. The objectives of the study are to find out indication of maintenance and shift of the language among the Batak Toba people in Pontianak, to explain the factors that cause the language shift, and to suggest efforts to maintain the language undergoing the shifting. Based on Domain Analysis of language use, a set of questionnaire delivered to 201 respondents had been applied to this study. That amount equals to 10% of total population of Batak Toba people in Pontianak. The questionnaire covered respondents’ background, language skill, and language choice of nine domains. Based on Speech Accommodation Theory, an observation was also made to the people to collect the use of their natural language in Pontianak. To compare the level of language skill and choice, the respondents have been divided based on generations. They are: 1) First comer to Pontianak, male and female, of 65 years or above, is called first generation (abbreviated G I) 2) Successors of first generation, male and female, born in Pontianak, is called second generation (abbreviated II ), 3) Successors of second generation, male and female, born in Pontianak, of minimum of 12 years, is called third generation (abbreviated G III). The quantitative data analyzed using Statistical Package for Social Science for Windows (SPSS) to get the level of frequency and mean score of the percentage of the background, language skill and language choice of the respondent. Based on quantitative data, it was found out that the language skill of Batak Toba decreases by G II and even more decreases by G III. Meanwhile, the Indonesian skill even more increases and increases by G II dan G III. And so is language choice. The G II and G III have used Indonesian more frequently compared to Batak Toba language. It means the Batak Toba language has shifted to Indonesian as lingua franca. Furthermore based on observation, the fact was found out that old generation has accommodated young generation to speak Indonesian. Moreover, another Batak Toba people observed, has also done the accommodation using Indonesia among Batak Toba people and to interlocutor of other communities. In connection with Crystal (2000) formula on language death classification, it can be said that Batak Toba language in Pontianak has been by the level of Endangered Language, that is the language that is treated dead due to the decreasing of the language acquisition speakers. Even according to Grenoble & Whaley (2006: 18) the Batak Toba language has been by the level of Disappearing, that is shifted to other language in community where the language is spoken, less in heritance among generations, limited usage in domain set, and wider language communication starts to change the language at home. If the situation is ignored over and over, therefore it is estimated that within two or three generation to go, there will be no more generation that able to speak Batak Toba language in Pontianak.